Apoptotic responses of zebrafish (Danio rerio) after exposure with microcystin‐LR under different ambient temperatures. Issue 8 (9th March 2012) - Ji, Wei; Liang, Hualei; Zhou, Wenshan; Zhang, Xuezhen
ABSTRACT Microcystins (MCs) can cause evident hepatic apoptosis. In vitro studies indicated that uptake of MC by isolated hepatocytes was dramatically reduced as ambient temperature dropped, and some studies presented a hypothesis that differences in core body temperatures in animals result in diverse uptake of MC, as well as different toxic effects. Thus far, however, few in vivo studies have been conducted to investigate the effects of temperature on MC‐induced hepatocyte apoptosis in fish, a typical poikilotherm. In the present study, zebrafish were treated with MC‐LR, an MC metabolite, at three water temperatures (12, 22 and 32 °C), and evident differences in apoptotic profiles were observed. Damage to liver ultrastructures revealed temperature‐dependent early‐stage patterns of apoptosis. Flow‐cytometric analysis indicated that hepatocyte apoptotic rates varied with a temperature‐dependent effect. The transcription levels of some apoptosis‐related genes were determined using quantitative real‐time polymerase chain reaction, and significantly elevated gene expressions of P53, Bcl‐2, Bax and caspase‐3 were found in the 12 and 32 °C groups. Results of the present study indicate that different ambient temperatures can lead to various toxic effects of MCs on hepatic apoptosis in fish. Copyright © 2012 John Wiley & Sons, Ltd.